Randomised controlled trial of analgesia for the management of acute severe pain from traumatic injury: study protocol for the paramedic analgesia comparing ketamine and morphine in trauma (PACKMaN) - Michelet, F; Smyth, M; Lall, R; Noordali, H; Starr, K; Berridge, L; Yeung, J; Fuller, G; Petrou, S; Walker, A; Mark, J; Canaway, A; et al. (BioMed Central, 2023)
Background Prehospital analgesia is often required after traumatic injury, currently morphine is the strongest parenteral analgesia routinely available for use by paramedics in the United Kingdom (UK) when treating patients with severe pain. This protocol describes a multi-centre, randomised, double blinded trial comparing the clinical and cost-effectiveness of ketamine and morphine for severe pain following acute traumatic injury.